ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN KINERJA KEUANGAN PENGEMBANGAN PRODUK BARU USAHA MIKRO KECIL DAN MENENGAH - Perminas Pangeran (Jurnal Riset Manajemen dan Bisnis, 2012)
ABSTRACT This study examines the effect of two strategic orientations, market orientation and entrepreneurial orientation, on financial performance in new product development. Drawing upon a sample of 137 micro, small, and medium-sized firms, multiple regression was used for testing four hypotheses. The results show that a market orientation and risk taking were positively related to financial performance in new product development, while innovativeness and risk taking show no such relationship. Keywords: market orientation, entrepreneurial orientation, and new product